Atomic-scale modeling of elementary processes during the fatigue of metallic materials: from crack initiation to crack-microstructure interactions - Möller, Johannes; Bitzek, Erik (Fatigue of Materials at Very High Numbers of Loading Cycles - Experimental Techniques, Mechanisms, Modeling and Fatigue Life Assessment, 2018)
It is well known that the fatigue of metallic materials is governed by the accumulation of plastic slip, which ultimately leads to the initiation and propagation of cracks. Whether a material exhibits an infinite fatigue life or not is therefore determined by the complex interplay between plastic deformation processes, the formation of small crack nuclei and the direct and indirect interactions of cracks with the surrounding microstructure. It is this complex interplay with the microstructure that makes predictive modeling of fatigue in metals such a arduous task, even though the first empirical expressions for the fatigue life have been developed more than hundred years ago. For this reason, most macroscale material models for large-scale computer simulations are still directly parameterized through costly fatigue experiments instead of considering microstructural information and lower-scale deformation mechanisms. The focus of this work is therefore to investigate the fundamental mechanisms that are of relevance to metal fatigue: crack nucleation by slip accumulation at grain boundaries (GBs), crack propagation along GBs, dislocation-crack interactions, and the influence of crack front curvature, which is especially important as long as the cracks are very small. Studying the direct defect-defect interactions characteristic for these processes require atomic-scale resolution. Atomistic modelling methods, such as molecular dynamics (MD) simulations, are therefore ideally suited for their close and detailed investigation. Since atomistic simulations come with their own challenges in terms of limited time and length scale, it is important to note that the present work is intended to lay the foundations for the future developments of predictive, mechanism-based and microstructure-sensitive material models for large-scale fatigue simulations, rather than being by itself quantitatively predictive. Instead, we present several qualitative and semi-quantitative observations, which should also hold true in real materials. I.e., that dislocation pile ups are more critical for crack nucleation at GBs than homogeneously distributed dislocations and vacancies; that furthermore, the fracture behavior and toughness is markedly influenced by (i) crystal orientations, (ii) GB structures, (iii) pre-existing dislocations, and (iv) crack front curvature.Finally, future directions for atomistic modeling of fatigue damage are presente
Keywords: Atomistic simulations; fracture; fatigue; grain boundaries; dislocations